2014
DOI: 10.1002/eji.201344180
|View full text |Cite
|
Sign up to set email alerts
|

Human bone marrow contains a subset of quiescent early memory CD8+ T cells characterized by high CD127 expression and efflux capacity

Abstract: Even today it is still not completely understood how CD8+ T-cell memory is maintained long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…This notion is supported by the different proliferation rates of CCR7-deficient and -sufficient CTL in mice that lack either IL-7 or IL-15, respectively [33]. Notably, T EM and T CM in human peripheral blood had a higher turnover as compared with the terminally differentiated T EMRA subset [42], and similar findings were reported for CD8 + T-cell subsets analyzed by Ki-67 staining in human BM [43]. Radbruch and colleagues reported that the fraction of Ki-67 + proliferating cells was significantly higher in CD4 + and CD8 + human memory T cells in peripheral blood, compared to the BM of the same individuals [44], and more prominent in cells that lacked IL-7Rα or CD69 expression.…”
supporting
confidence: 63%
“…This notion is supported by the different proliferation rates of CCR7-deficient and -sufficient CTL in mice that lack either IL-7 or IL-15, respectively [33]. Notably, T EM and T CM in human peripheral blood had a higher turnover as compared with the terminally differentiated T EMRA subset [42], and similar findings were reported for CD8 + T-cell subsets analyzed by Ki-67 staining in human BM [43]. Radbruch and colleagues reported that the fraction of Ki-67 + proliferating cells was significantly higher in CD4 + and CD8 + human memory T cells in peripheral blood, compared to the BM of the same individuals [44], and more prominent in cells that lacked IL-7Rα or CD69 expression.…”
supporting
confidence: 63%
“…For example, a high proportion of BM memory CD4 and CD8 T cells express CD69 ( 22 , 23 , 32 ). Moreover, memory CD8 T cells from both mouse and human BM have a lower membrane expression of CD127, i.e., the IL-7Rα chain ( 8 , 22 , 59 , 61 ), with the exception of antigen-specific CD8 T cells from lymphocytic choriomeningitis virus (LCMV)-infected mice ( 23 ). The TNF-R family member GITR is selectively upregulated by a fraction of mouse BM memory CD8 T cells ( 56 ).…”
Section: Bone Marrow Memory T Cellsmentioning
confidence: 99%
“…Recent work suggests that MDR1 is expressed in the bone marrow by a quiescent population of early memory CD8 + T cells that proliferates efficiently in vitro in presence of viral peptides. 70 Turtle et al . also reported a memory CD8 + T cell subset (IL18Rα + CD161 + CD62L ± ) with high MDR1 expression endowed with stem cell properties and able to withstand high doses chemotherapy.…”
Section: Introductionmentioning
confidence: 99%